DESCRIPTIVE STUDY OF MODES AND TECHNIQUES OF INTERPRETING USED BY INTERPRETERS AT POTTER'S HOUSE CHRISTIAN MINISTRIES - Anakay, Picessylia S.; Ludji, Ifoni; Marpaung, Tiarma (Journal of Language, Education, Literature, and Culture, 2024)
This study aims to identify and describe the modes and techniques used by interpreters in the process of interpreting sermons at Potter's House Christian Ministries. This research is a descriptive qualitative study. This research employed the scrutinizing method for data collection, which entails attentive listening to language usage (Sudaryanto, 1993: 133). The researcher adopted a non-participatory role, serving as mere observer of data without direct involvement in its formation. The study focused on analyzing language usage in two recorded videos of weekly services at Potter's House Christian Ministries. The researcher specifically examined individual sentences as manifestations of data, which were recorded and organized into tables based on criteria such as perspective, vocabulary, and modality. Technique assessment was employed to gather data and assess the impact of different modes and techniques on interpretation. The study reveals that interpreters at Potter's House Christian Ministries primarily employ consecutive interpreting mode, particularly short consecutive interpreting. The researcher also discovered six predominant techniques used during the interpretation process, namely: (1) reformulation, (2) elimination technique, (3) summarization, (4) error correction technique, (5) metaphors and saying technique, and (6) code-switching technique.